Era of ignition : coming of Age in a Time of Rage and Revolution - Tamblyn, Amber (Crown Archetype, 2019)
"A passionate manifesto with personal stories, anecdotes, and opinions from the front lines of modern American womanhood from actor, filmmaker, and activist Amber Tamblyn"--